Text Compression & Encryption Method Based on RNA and MTF - Gbashi, Ekhlas Khalaf (Iraqi Journal of Science, 2022)
The sending of information at the present time requires the speed and providing protection for it. So compression of the data is used in order to provide speed and encryption is used in order to provide protection. In this paper a proposed method is presented in order to provide compression and security for the secret information before sending it. The proposed method based on especial keys with MTF transform method to provide compression and based on RNA coding with MTF encoding method to provide security. The proposed method based on multi secret keys. Every key is designed in an especial way. The main reason in designing these keys in special way is to protect these keys from the predication of the unauthorized users.